Two new species of Pluteus (Pluteaceae, Agaricales) from Inner Mongolia, China - Liu, Mu; Bau, Tolgor (Phytotaxa, 2025)
Based on morphological and phylogenetic analyses, two new species of Pluteus were discovered in Inner Mongolia, China: Pluteus daqinggouensis and P. liaoheensis. P. daqinggouensis is characterized by a pileus with a rugose center and striate margin, broadly clavate or ellipsoid cheilocystidia, fusiform or nearly cylindrical pleurocystidia, sometimes slightly constricted in the center. The characteristics of P. liaoheensis include a brown or dark brown pileus with radical dark brown hairs, pleurocystidia rare or absent, and a trichodermal to intricate trichodermal pileipellis, composed of clavate, cylindrical, fusiform elements. Phylogenetic analyses of ITS datasets, conducted using Maximum Likelihood and Bayesian methods, placed both new species within Pluteus sect. Celluloderma. Morphological descriptions and line illustrations of new species are provided.